EP278 Atypical presentation of cardiac metastasis in uterine cervical cancer. (1st November 2019) - da Silva Dias, D; Gosalbez, B
Abstract : Introduction/Background: Uterine Cervical cancer (UCC) represents 6% of gynecological malignant tumors. Cardiac metastasis of UCC are extremely rare as only 4% of them are diagnosed antemortem. The epidemiology and clinical manifestations are not clearly known, only a small number of clinical case reports are published in the literature. The overall survival is expected to be lower than 12 months. Methodology: Clinical case report with the objective to raise awareness of a rare presentation of cardiac metastasis in UCC. Results: Woman with 56 years years old is presented, with diagnosis of UCC, stage IIB in May 2014. Proposed to concurrent chemo-radiotherapy (CCRT) which she refused. In February 2015 visited the emergency department with obstructive kidney failure due to bilateral ureter hydronephrosis. Bilateral nephrostomies were applied, and the patient started treatment in May 2015 with CCRT, cisplatin 40 mg/m 2 and external radiotherapy. Patient had no indication for brachytherapy. In February 2017 presented progressive asthenia and anemia G1 due to radiation proctitis. A computed tomography scan in follow up consultation was performed presenting a lesion of 9cm in the right ventricle with the differential diagnosis of metastasis versus thrombus. A trans-thoracic echocardiogram was performed showing a mass in the right ventricle (RV) without dysfunction of the RV nor left ventricle (LVEF 58%). A magnetic resonance was performed as well to better identify the lesion. After collaboration with a cardiac surgery center no surgical procedure was possible. The patient was discharged and started palliative chemotherapy with Carboplatin and paclitaxel but unfortunately succumbed to disease 4 months later. Conclusion: The present case report is relevant to raise awareness on a rare, but still possible site of metastasis of uterine cervical cancer. Disclosure: Nothing to disclose.